1982
DOI: 10.1021/bi00263a002
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and crystallographic data for phaseolin, the storage protein from Phaseolus vulgaris

Abstract: We have isolated and biochemically characterized a major seed protein from Phaseolus vulgaris (common garden green bean) that appears to be identical with a form of the storage protein of that plant seed known as phaseolin. We have further shown that it appears very similar in most properties to the storage protein from Canavalia ensiformis (jack bean) which we have solved to 3.0-A resolution using X-ray diffraction techniques. [McPherson, A., & Rich, A. (1973) J. Biochem. (Tokyo) 74, 155-160; McPherson, A., &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In fact, it is possible to observe the presence of phaseolin crystals of quasi-cubic symmetry on the surface of the film containing unmodified phaseolin. These crystal morphologies are common to a large number of other varieties of seed-storage proteins when extracted under acidic conditions . Interestingly, SEM revealed that, in the film obtained in the presence of TG, phaseolin crystals are not evident, suggesting that the action of the enzyme on the globular protein affects its 3D structure.…”
Section: Resultsmentioning
confidence: 95%
“…In fact, it is possible to observe the presence of phaseolin crystals of quasi-cubic symmetry on the surface of the film containing unmodified phaseolin. These crystal morphologies are common to a large number of other varieties of seed-storage proteins when extracted under acidic conditions . Interestingly, SEM revealed that, in the film obtained in the presence of TG, phaseolin crystals are not evident, suggesting that the action of the enzyme on the globular protein affects its 3D structure.…”
Section: Resultsmentioning
confidence: 95%
“…It is very interesting that the & preparation modified by limited proteolysis was more easily crystallized than the native /%. The previous investigations on two vitellins, canavalin from jack bean and phaseolin from French bean, showed that these two storage proteins were cleaved specifically at a single site between two major domains with retention of the quaternary structures of the vicillin trimers, and the products could be crystallized more easily than the native proteins (22,23). The cleaved site on the /?…”
Section: Substrate Specificity On Peptide-mca Substrates-mentioning
confidence: 98%
“…Common bean ( Phaseolous vulgaris L.) SPC ranges from 20 to 30% [ 25 , 26 ], and plays a pivotal role in mitigating protein-related malnutrition, especially in underdeveloped countries [ 46 , 47 ]. The major storage protein in common bean is phaseolin, accounting for 36–46% of total seed proteins [ 48 ], with 50–60% of the phaseolin belonging to the 7S vicilin class, insufficient in methionine, cysteine, and tryptophan essential amino acids [ 49 , 50 , 51 ].…”
Section: Grain Legumes As An Important Source Of Dietary Proteinmentioning
confidence: 99%